Conditional cause-specific survival after chemotherapy and local treatment for primary stage IV breast cancer: A population-based study - Xiao, Min; Zhang, Pin (Frontiers in Oncology, 2022)
Background: Conditional survival (CS) represents the probability of surviving for additional years after the patient has survived for several years, dynamically describing the survival rate of the patient with the varying time of survival. The aim of this study was to evaluate the conditional cause-specific survival (CCSS) after chemotherapy and local treatment for metastatic breast cancer, and identified the prognostic factors affecting the CCSS. Methods: Patients diagnosed with primary stage IV breast cancer in the Surveillance, Epidemiology, and End Results (SEER) database from 2010 to 2015 were included. CS is defined as the probability of additional survival for y years after the patient had survived x years with the calculation formula CCSS (x | y) = CSS (x + y)/ CSS (x), CSS(x) indicates that the patient's cause-specific survival rate at the time of x years. Cox proportional hazards models were used to evaluate predictors of CCSS. Results: 3,194 patients were included. The 5-year CSS was 39%, while the 5-year CCSS increased to 46%, 57%, 71%, 85% after the diagnosis of 1, 2, 3, and 4 years. For patients with adverse clinical pathological features, CCSS had more pronounced increase with survival time and is more different from the CSS at diagnosis. No matter at the time of diagnosis, 1 year or 3 years after diagnosis, HER2 status, local treatment, and multisites metastasis were independent prognostic factors that affect the long-term survival of patients (all P <0.05). Conclusion: The 5-year CCSS of patients with stage IV breast cancer was extended as the survival years increased. HER2 status, multisites metastasis and local treatment were independent prognostic factors even 3 years after diagnosis.